PENGARUH IMPLEMENTASI ANGGARAN PARTISIPATIF, TRANSPARANSI, AKUNTABILITAS DAN ANGGARAN BERBASIS KINERJA TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH - Herlia, Meta; Fachruzzaman, Fachruzzaman; Baihaqi, Baihaqi (JURNAL FAIRNESS, 2013)
This study examined the effect of the implementation of participatory budgeting, transparency, accountability, and performance-based budgeting to performance Unit (SKPD) Bengkulu provincial government. The study was a descriptive survey method. Data were obtained from the employee personnel involved in budget preparation on all SKPD in Bengkulu province government. Data obtained using a questionnaire given to the respondents directly. Based on data from 56 respondents who participated in the study, the research found that the simultaneous implementation of participatory budgeting, transparency, accountability, and performance-based budgeting affect the performance of the Regional Working Units (SKPD) Bengkulu provincial government. Only partial implementation of transparency and performance-based budgeting that have a significant positive impact on the performance of the government on education Bengkulu province.